Undergraduates' interpretation on WhatsApp smiley emoji - Subashini Annamalai,; Sobihatun Nur Abdul Salam, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Undergraduate students, who are digital native, are keen on using emoji (smileys and ideograms) frequently to express themselves emotionally in their digital communication such as WhatsApp Messenger. Nevertheless, sometimes, they got into misunderstanding due to the different emoji's interpretation between the sender and the recipient. Research investigating emoji is still relatively new and this study discusses the diverse interpretations of WhatsApp emoji specifically the smileys among Malaysian undergraduates in a public university. This study attempted to investigate 210 undergraduates' interpretations of 75 smiley (face-like) meanings in WhatsApp Messenger. The respondents were asked to give feedback in self-administrated survey questionnaire to gather information on their interpretation of the smileys used in WhatsApp. A descriptive analysis was conducted on the students' interpretations and the findings disclosed that although the students interpreted a few smileys correctly, they did not know the intended meaning of most of the smileys correctly. The results of this study suggested that the students should know the meaning of the smiley/ emoji used in their digital conversation to able to understand its intended use and to avoid miscommunication in their digital communication. For WhatsApp users, the findings will be beneficial to emphasize the need to understand the emoji's intended meaning for future tolerant and wiser use.